“Everybody’s problem but nobody’s problem”: Qualitative study on integrating smoking cessation and mental health services in Singapore - Yee Ling Lok; Grace Ping Ping Tan; Mythily Subramaniam; Yvette van der Eijk (PLoS ONE, 2025)
Background Although quitting smoking benefits mental health, people with mental health conditions tend to have higher smoking rates and more severe tobacco use disorders. Integration of smoking cessation into mental healthcare, or vice versa, could help to meet the needs of this population. While Singapore offers specialist smoking cessation and mental health services, it is unclear how these services address the needs of people with comorbid tobacco use and mental health issues. This study aimed to explore the integration of smoking cessation and mental health services in Singapore from the perspective of healthcare professionals. Methods We conducted one-on-one semi-structured interviews with 21 Singaporean health professionals with expertise in mental health (n = 5), smoking cessation (n = 5), primary healthcare (n = 3), specialist respiratory or emergency care (n = 3) or health systems and policy (n = 5). We recruited participants from the authors’ professional networks and subsequently via snowballing. We used inductive coding methods to identify themes that emerged from the data. Results Health professionals were divided on whether smoking and mental health are sufficiently interconnected to justify more integrated or tailored services. Smoking cessation and mental health were generally approached in a siloed manner, reflecting systemic barriers to integration as well as ranging levels of awareness among health professionals on the association between smoking and mental health. While some participants welcomed the integration of smoking cessation and mental health services as a more convenient, effective and equitable way to address the needs of this population, others deemed it unnecessary and viewed smoking as a lifestyle habit, distinct from other mental health issues. Implications There is a need to educate health professionals on smoking as a mental health issue and to consider more tailored programmes designed to address smoking cessation and mental health needs simultaneously.